Analisis Pengaruh Struktur Kepemilikan Terhadap Pengungkapan Modal Intelektual Dengan Kualitas Komite Audit Sebagai Variabel Pemoderasi: (Studi Empiris Pada Perusahaan Keuangan Yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020) - Wahyudi, Husni (DAS Institute, 2024)
Currently the disclosure of intellectual capital is still very minimal. One of the reasons is the characteristic of intellectual capital disclosure that is still voluntary, the difficulty of identifying, measuring, and reporting intellectual capital, and the absence of provisions, especially for large companies. The purpose of this study was to determine the effect of the quality of the audit committee as a moderator. This research is a type of quantitative research. The sample of this study is financial companies listed on the Indonesia Stock Exchange for the period 2016 to 2020. The sample was selected using the purposive sampling method and obtained 100 units of analysis which will be the object of research. Analysis using content analysis on financial statements uses SPSS 21 multiple regression analysis by fulfilling the classical assumption test. The results of this study prove that managerial ownership, institutional ownership, and government ownership have no partial and insignificant effect on intellectual capital disclosure. Meanwhile, foreign ownership has a positive and significant effect on the disclosure of intellectual capital. Testing of moderating variables shows that the quality of the audit committee strengthens the influence of managerial ownership, government ownership, and foreign ownership on intellectual capital disclosure. While the quality of the audit committee does not strengthen the influence of institutional ownership on intellectual capital disclosure